2021
DOI: 10.24093/awej/vol12no4.6
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Translation during COVID-19 Outbreak: Challenges and Discoveries

Abstract: The present paper addresses translation teaching during the COVID-19 outbreak, seeking to discover the challenges translation teachers encounter in online education and the solutions available to resolve them. Its importance springs from the fact that teaching almost all over the world had to depend on distant teaching/learning through electronic platforms to face the pandemic of COVID-19. Therefore, the present study seeks to discover the challenges encountered in online translation teaching and the proposed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Still, some recent studies have already indicated findings similar to the results of this research paper. Even though not particularly in the field of translation in general and sight translation in particular, the considerable decrease in students' academic achievement during the COVID-19 pandemic has also been reported by some researchers such as Moliner, et al, (2022), Alghamdi (2021), Alwazna, (2021 and Gonzalez, et al (2020). Consequently, the reduction in students' sight translation achievement found in the current paper study is too similar to studies in teaching and learning in general and translation teaching and learning in particular.…”
Section: Discussionmentioning
confidence: 79%
“…Still, some recent studies have already indicated findings similar to the results of this research paper. Even though not particularly in the field of translation in general and sight translation in particular, the considerable decrease in students' academic achievement during the COVID-19 pandemic has also been reported by some researchers such as Moliner, et al, (2022), Alghamdi (2021), Alwazna, (2021 and Gonzalez, et al (2020). Consequently, the reduction in students' sight translation achievement found in the current paper study is too similar to studies in teaching and learning in general and translation teaching and learning in particular.…”
Section: Discussionmentioning
confidence: 79%
“…Research from Alwazna (2021) , on the other hand, does not appear to support this. In this study, a questionnaire including both closed-ended and open-ended questions was used to gain a better understanding of sixty translation teachers’ online teaching experiences during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Sin embargo, la mayoría de los estudiantes se enfrentaron a diversos problemas tecnológicos, didácticos y de salud que interfirieron en su proceso de aprendizaje, lo que aumentó su deseo de volver a las clases regulares en la universidad lo antes posible. Alwazna (2021), desde Arabia Saudí, aborda la enseñanza de la traducción durante la pandemia. Trata de descubrir los retos que encuentran los profesores de traducción en la combinación árabe-inglés en la enseñanza en línea y las soluciones disponibles para resolverlos.…”
Section: Palabras Claveunclassified